The potential of online bulletin platforms for language teaching in classrooms / Aini Faridah Azizul … [et al.] - Azizul, Aini Faridah; Ismail, Munirah Izzati; Othman, Pishaza; Wan Azlan, Wan Ainin Sofiya (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
This study investigates the potentiality of implementing online bulletin platforms as a means of language acquisition for secondary school learners in Malaysia. Online bulletin platforms are mostly used by teachers to make their lesson plans more convenient and engaging. The research was conducted using quantitative methods by creating a survey for secondary school teachers and students. The survey evaluates the respondent’s perception on the potential of online bulletin platforms as a method of teaching. The research findings found that Padlet is the most preferred online bulletin platforms. In addition, it revealed that the platforms are effective in boosting one’s speaking skill, raising the confidence level among introverted students, organising and accessing teaching materials, assessing students’ work, and lastly, encouraging collaborative learning. In conclusion, online bulletin platforms are the most preferred e- learning tool used by teachers and students to aid the language acquisition process. The implementation of online bulletin platforms as the main method of teaching a language in Malaysian secondary schools can be implemented if the right tools, materials, and support are provided.